Excision of Different Oral Benign Exophytic Lesions With a Diode Laser: A Clinical Case Series - Gholizadeh, Narges (J Lasers Med Sci, 2020)
Introduction: Lasers are becoming the standard of care for many dental procedures, and are being introduced as a high-tech instrument. They are also becoming more routine in dentistry through the advent of office-based lasers, which are also simple to use within the oral cavity. Many studies have shown the competencies of laser technology for the management of benign oral lesions as these techniques allow for painless and bloodless oral surgery. Cases Report: Nine patients attending the Department of oral and maxillofacial Disease, Shahid Beheshti University of Medical Sciences, Tehran, Iran, underwent laser outpatient procedures for the surgical removal of a wide range of benign oral lesions. Regarding the history, present illnesses and clinical figures of all reported cases, the clinician ensured that the lesions were benign and after taking informed consent from every patient, he did complete the excision of lesions with diode lasers. Following the injection of local anesthesia, an 810 nm diode laser was applied for the excisional biopsy of oral lesions. The specimens were sent for histopathological evaluations and the patients were assessed on intraoperative and postoperative complications. The patients were followed up for postoperative complications at one week and 2 weeks post-treatment. Conclusions: According to our findings, a diode laser can be a choice for the outpatient treatment of oral mucosal benign lesions as this technique provides painless and almost bloodless treatment.